The history of Charles Jones, the footman - More, Hannah, 1745-1833 (Cheap repository., 1796)
The author tells the story of his own life, focusing on the Lord's gracious ways with him. By example, Charles shares the importance of honoring and serving his employer faithfully, and how any hopes of keeping his walk with God required him to watch who he made his companions.